Profit efficiency as a measure of performance and frontier models: A resource-based view - Antonio Arbelo; Marta Arbelo-Pérez; Pilar Pérez-Gómez (BRQ Business Research Quarterly, 2021)
Although the resource-based view (RBV) of the firm is one of the most accepted theories of strategic management, it has been criticized for its limited empirical support. The RBV basically predicts the relationship between the firm's resources and its performance. This study argues that it is more appropriate to measure firm performance using profit efficiency than traditional financial or accounting measures and that frontier models have great potential in empirical research on the RBV. To test this idea empirically, we used a stochastic frontier model with random coefficients to evaluate the impact of corporate reputation on profit efficiency. Finally, implications of the aforementioned focal points are discussed.
Keywords: C11; L25; M10; M20; 650; corporate reputation; performance measurement; profit efficiency; resource-based view; stochastic frontier methodology